KAJIAN KELAYAKAN PENGEMBANGAN USAHA PARIWISATA ALAM DIKAWASAN WANAWISATA NGRAPE KABUPATEN MADIUN - Susanto, Anang; Firmansyah, Firmansyah (JURNAL AGRI-TEK, 2014)
Potential crop production areas of teak forests and hilly land lanscap, clear stream is a natural tourism assets in the teak forests Grape potential and promise for more .Destination managed research: nature tourism feasibility .Calculate production forest area . and determine public perception with the nature of tourism development projects. This study uses Observation Technique, Survey technique, Survey, Data Processing Method using the formula: Net Present Value (NPV) /, Benefit Cost Ratio (BCR) /, Internal Rate of Retrun (IRR), Break Event Point (BEP) BCR Ngrape noted tourist interest rate of 12% for out-bound BCR of 3.6, 1.41 and 1.28 for the fishing to eat. boundr out IRR 25%, 29% fishing and restaurants 23%. IRR of more than 1% mean return capital projects approved in force will remain and have to be paid. Total capital of USD 54 million out bound covered in year three Rp58.400.000., Fishing facilities covered Rp 24.9 million to Rp 28.4 million to Rp mahan home fourth year 177.400.000t reached USD 159.2 million in the draw point in the fourth.Keyword: natural tourism, capital, potential, public, forest